Preparation method of polyacrylate foaming regulator
By adopting a three-layer core-shell structure and a photothermal double-initiation system, the contradiction between the melt strength of polyvinyl chloride and the inability to expand the bubbles is solved, and the more uniform foaming and performance improvement of the product is achieved.
Patent Information
- Application Number
- CN202510368542.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The contradiction between the strength of polyvinyl chloride melt and the inability to expand the bubbles leads to the product surface gloss, processing fluidity, and uniformity, and the thermal deformation temperature, strength and low temperature resistance are also affected.
A three-layer core-shell structure is adopted to form a high-rigid three-dimensional network through crosslinking agent to improve compressive strength and thermal deformation temperature; the intermediate layer introduces hydroxyethyl acrylate to enhance the interface binding force; the shell layer combines ethyl acrylate with dodecyl fluoroheptyl methacrylate to achieve superhydrophobic surface and high adhesion of the bottom layer.
The melt strength is improved while forming a more uniform cell structure, which solves the problem that bubbles cannot be expanded, improves the surface gloss, processing fluidity and uniformity of the product, and improves the thermal deformation temperature and mechanical properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of foaming regulators, and in particular to a method for preparing a polyacrylate foaming regulator. Background Art
[0002] Polyacrylate foaming regulator is a regulator that effectively increases the cohesion and homogeneity of polyvinyl chloride melt by increasing the pressure and torque of polyvinyl chloride melt, making the resulting polyvinyl chloride products denser. It has all the basic characteristics of general processing aids for polyvinyl chloride. The only difference from general processing aids for polyvinyl chloride is that the molecular weight of polyacrylate foaming regulator is much higher than that of general processing aids for polyvinyl chloride.
[0003] The main function of polyacrylate foaming regulator is to promote the plasticization of polyvinyl chloride; improve the melt strength of polyvinyl chloride foaming material, prevent the merging of bubbles, so as to obtain uniformly foamed products; ensure that the melt has good fluidity, so as to obtain products with good appearance.
[0004] The key factor to increase the weight of PVC foam sheet is to increase the melt strength of PVC. There are many ways to increase the melt strength of PVC, but the most effective way is to add polyacrylate foaming regulator. Generally speaking, the higher the viscosity of the polyacrylate foaming regulator, the more obvious the effect of improving the melt strength. However, high-viscosity polyacrylate foaming regulator will cause the bubbles in the PVC melt to be unable to expand, thereby affecting the surface gloss, processing fluidity and uniformity of the PVC product. In addition, it will also indirectly affect the heat deformation temperature, strength and low temperature resistance of PVC. Summary of the invention
[0005] In order to solve the above-mentioned technical problems, the present invention provides a method for preparing a polyacrylate foaming regulator. The method adopts a three-layer core-shell structure to improve the melt strength while forming a more uniform pore structure, thereby solving the contradiction between the melt strength of polyvinyl chloride and the inability of bubbles to expand; by adopting a dynamic emulsification method, the emulsion particle size is effectively controlled, the uniformity of the regulator component is improved, and the problems of uneven melt bubbles and low closed cell rate are solved; by adopting a photothermal dual initiation system, the reaction time is shortened, and the problem of low synthesis efficiency is solved. The method is specifically achieved through the following technical solutions.
[0006] The present invention provides a method for preparing a polyacrylate foaming regulator, comprising the following steps: S1, methyl methacrylate, butyl acrylate and divinylbenzene are mixed to form a core layer monomer composition for later use; S2, mixing isooctyl acrylate, styrene, and hydroxyethyl acrylate to form an intermediate layer monomer composition for later use; S3, mixing ethyl acrylate and dodecafluoroheptyl methacrylate to form a shell monomer composition for later use; S4, mixing sodium lauryl sulfate and octylphenol polyoxyethylene ether to form an emulsifier for standby use; S5, mixing the core layer monomer composition, the emulsifier and the deionized water, and stirring for pre-emulsification for 10 minutes; S6, adding emulsifier three times, each time with an interval of 20 minutes, to obtain a nuclear layer pre-emulsion; S7, adding ammonium persulfate to the core layer pre-emulsion, heating to 75° C. and reacting for 1 h to obtain a core layer prepolymer; S8, adding the middle layer monomer composition, hexamethylphosphoric triamide and TPO initiator to the core layer prepolymer, prepolymerizing under ultraviolet light, then heating to 65° C., adding ammonium persulfate and continuing the reaction for 2 h to obtain a double-layer prepolymer; S9, mixing the shell monomer composition with an emulsifier to prepare a shell pre-emulsion, adding the shell pre-emulsion to the double-layer prepolymer 4 times, each time at an interval of 30 minutes, and reacting at 70° C. for 3 hours to obtain a three-layer prepolymer; S10, cooling to room temperature, filtering, and adjusting the solid content to 40% to 45% to obtain the target product.
[0007] Preferably, in step S1, the mass ratio of methyl methacrylate, butyl acrylate and divinylbenzene is 60-80:20-30:0.5-2.
[0008] Preferably, in step S2, the mass ratio of isooctyl acrylate, styrene and hydroxyethyl acrylate is 10-14:4-6:1-2.
[0009] Preferably, in step S3, the mass ratio of ethyl acrylate to dodecafluoroheptyl methacrylate is 7-9:1-3.
[0010] Preferably, in step S4, the mass ratio of sodium dodecyl sulfate to octylphenol polyoxyethylene ether is 1:2-4.
[0011] Preferably, in step S5, the mass ratio of the core layer monomer composition, the emulsifier, and the deionized water is 15-20:1-1.2:250-350.
[0012] Preferably, in step S5, the stirring speed is 8000-12000 r / min.
[0013] Preferably, in step S6, the mass ratio of the emulsifier added each time to the core layer monomer composition in step S1 is 1:40-50.
[0014] Preferably, in step S9, the mass ratio of the shell monomer to the emulsifier is 10-15:1.
[0015] After adopting the above technical solution, the beneficial effects of the present invention are: 1. A three-layer core-shell structure is adopted. The core layer forms a high-rigidity three-dimensional network through a cross-linking agent to improve the compressive strength and heat deformation temperature. Hydroxyethyl acrylate is introduced as a functional monomer in the middle layer to enhance the interfacial bonding strength. The shell layer combines the flexibility of ethyl acrylate with the fluorinated chain segment of dodecafluoroheptyl methacrylate to achieve super hydrophobic surface and high adhesion to the bottom layer.
[0016] 2. Use sodium dodecyl sulfate and octylphenol polyoxyethylene ether to reduce the critical micelle concentration and the total amount of emulsifier used; by adding emulsifier in batches to refine the latex particles, the stability of the emulsion is improved, and the phased polymerization and gradient distribution are achieved.
[0017] 3. A photothermal dual initiation system is used, and ultraviolet light is used in the pre-polymerization stage of the middle layer to quickly cure the surface and shallow monomers, forming a dense cross-linked network and shortening the reaction time; subsequent thermal initiation is used to penetrate deep unreacted areas, thereby improving the conversion rate and reducing residual monomers. DETAILED DESCRIPTION
[0018] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.
[0019] An embodiment of the present invention provides a method for preparing a polyacrylate foaming regulator, comprising the following steps: S1. Based on the sum of parts by weight being 100, 60 to 80 parts by weight of methyl methacrylate, 20 to 30 parts by weight of butyl acrylate, and 0.5 to 2 parts by weight of divinylbenzene are mixed to prepare a core layer monomer composition; Among them, divinylbenzene is used here as a cross-linking agent. In this process, the divinyl structure of divinylbenzene can be copolymerized with the monomers of methyl methacrylate and butyl acrylate in free radical polymerization, connecting different polymer chains through chemical bonds to form a three-dimensional cross-linked network.
[0020] The cross-linked structure limits the free movement of molecular chains, which can significantly increase the glass transition temperature and mechanical strength of the polymer, prevent the collapse of the pore walls due to softening during the foaming process, and the cross-linked network enhances the melt elasticity, making it easier for the material to remain stable during high shear processing and reducing pore merging or rupture.
[0021] At the same time, the microscopic heterogeneity of the cross-linking points can be used as sites for bubble nucleation, promoting uniform nucleation of the pores and avoiding local excessive foaming or collapse.
[0022] S2. Based on the sum of parts by weight being 100, 50 to 70 parts by weight of isooctyl acrylate, 20 to 30 parts by weight of styrene, and 5 to 10 parts by weight of hydroxyethyl acrylate are mixed to prepare an intermediate layer monomer composition; In the above steps, hydroxyethyl acrylate is added to isooctyl acrylate and styrene as a functional monomer, mainly utilizing the hydroxyl characteristics of hydroxyethyl acrylate, which can form hydrogen bonds or covalent bonds with polar groups (such as carboxyl groups, epoxy groups) of the core layer or shell layer, thereby strengthening the interfacial bonding force of the core-shell structure.
[0023] In addition, hydroxyethyl acrylate is used in the middle layer, and its molecular chain can further improve the mechanical interlocking between the core and the shell through entanglement or adsorption, play a physical anchoring effect, thereby enhancing the stability of the overall structure and reducing the risk of interlayer delamination.
[0024] S3, based on a total of 100 parts by weight, 70 to 90 parts by weight of ethyl acrylate and 10 to 30 parts by weight of dodecafluoroheptyl methacrylate are mixed to prepare a shell monomer composition; The fluorinated monomer dodecafluoroheptyl methacrylate is mixed with ethyl acrylate as the shell structure, which, due to the unique properties of fluorine atoms, gives the core-shell structure polymer significant functional advantages and performance improvements.
[0025] The long fluorocarbon chain of dodecafluoroheptyl methacrylate can significantly reduce the surface energy of the material, making the shell layer highly hydrophobic or even super hydrophobic, effectively repelling water, oil and pollutants. A micro-nano structure similar to the "lotus leaf effect" is formed on its surface, making it difficult for stains to adhere.
[0026] The high bond energy and low polarizability of the carbon-fluorine bond in dodecafluoroheptyl methacrylate make the shell extremely resistant to acids, alkalis, solvents and oxidants, which can effectively extend the service life of the material in corrosive environments. In addition, the shielding effect of fluorine atoms can absorb ultraviolet rays and reduce the photodegradation of the polymer main chain, thereby greatly improving the weather resistance of the melt.
[0027] In addition, the fluorine-containing shell layer has both high-temperature stability and flame retardancy. The fluorine-containing shell layer maintains structural integrity at high temperatures and delays thermal decomposition. The fluorine element can inhibit the free radical chain reaction during the combustion process and reduce the flammability of the material.
[0028] S4, compounding sodium lauryl sulfate and octylphenol polyoxyethylene ether in a mass ratio of 1:2-4 to form an emulsifier for standby use; Sodium dodecyl sulfate is an anionic surfactant, and octylphenol polyoxyethylene ether is a non-ionic surfactant. The combination of the two as an emulsifier system can significantly improve the emulsification efficiency and product performance through synergistic effect in the emulsion polymerization of core-shell structured polymers.
[0029] The dual effects of charge repulsion of sodium dodecyl sulfate and steric hindrance of octylphenol polyoxyethylene ether can significantly improve the stability of the emulsion.
[0030] S5, mixing the core layer monomer composition, the emulsifier and the deionized water in a mass ratio of 15-20:1-1.2:250-350, and pre-emulsifying for 10 minutes under high-speed shearing; S6, adding emulsifier three times during the polymerization process, the mass ratio of the emulsifier added each time to the core layer monomer composition is 1:40-50, each time interval is 20min, and the core layer pre-emulsion is obtained; The combination of sodium dodecyl sulfate and octylphenol polyoxyethylene ether can quickly reduce interfacial tension, form small and evenly distributed monomer droplets, provide uniform nucleation sites for core layer polymerization, and the steric hindrance of octylphenol polyoxyethylene ether slows down the migration of monomers from small droplets to large droplets, maintaining the uniformity of the core layer particle size.
[0031] Sodium dodecyl sulfate can form a strong electric double layer on the core surface to resist the collision and aggregation of latex particles in the early stage of polymerization. Combined with the PEO chain of octylphenol polyoxyethylene ether, it further enhances the spatial barrier. At the same time, under high speed conditions and by adding emulsifiers in batches, the emulsion particle size can be effectively controlled to 80-150nm.
[0032] Among them, the stirring rotation speed is 8000-12000r / min.
[0033] S7, adding 0.5% to 1.5% of the total weight of the core layer monomer composition of ammonium persulfate to the core layer pre-emulsion, heating to 75° C. and reacting for 1 hour to obtain a core layer prepolymer; Ammonium persulfate is a water-soluble initiator. Free radicals are mainly generated in the water phase and start polymerization by diffusing into monomer droplets or micelles. When heated to 60-80°C, ammonium persulfate decomposes to generate sulfate radicals, which then initiate a chain polymerization reaction of the monomers through free radicals.
[0034] S8, adding 30% to 50% of the total weight of the intermediate layer monomer composition, 0.5% to 2% of the total weight of the core layer monomer composition, and 1% to 3% of the total weight of the TPO initiator to the core layer prepolymer, prepolymerizing under ultraviolet light, then heating to 65° C., adding 0.5% to 1.5% of the total weight of the core layer monomer composition, and continuing the reaction for 2 hours to obtain a double-layer prepolymer; Wherein, the TPO initiator is trimethylbenzoylphosphine oxide.
[0035] Among them, ultraviolet irradiation is achieved by a 50W LED ultraviolet lamp, and the irradiation time is 30 minutes.
[0036] In the above steps, ultraviolet light initiated polymerization is firstly realized, and ultraviolet light promotes the TPO initiator to generate free radicals, which further initiates the copolymerization reaction of the monomers acrylate, styrene and hydroxyethyl acrylate in the middle layer monomer.
[0037] In the above process, hexamethylphosphoric acid triamide can improve the monomer solubility and chain segment activity, promote polymerization uniformity, and achieve uniform dispersion of the intermediate layer monomer on the surface of the core layer.
[0038] Moreover, hexamethylphosphoric acid triamide can prolong the life of free radicals through coordination, thereby increasing the polymerization rate and molecular weight.
[0039] Ultraviolet light triggers local polymerization or cross-linking of the middle layer monomers to form a preliminary interface structure. Incompletely reacted monomers or insufficiently cross-linked areas may remain, which need to be further cured through subsequent thermal reactions.
[0040] The reaction system was heated to 65°C and ammonium persulfate was added to react for 2 hours. The polymerization of the unreacted monomers was continuously initiated through thermally induced supplementary polymerization and crosslinking, thus compensating for the limitations of the ultraviolet light stage.
[0041] Usually the rapid decomposition temperature of ammonium persulfate is 70°C. Here, a decomposition temperature of 65°C is used to avoid explosion caused by violent reaction and ensure the continuous generation of free radicals.
[0042] This step uses a combination of photothermal and dual initiation systems. Ultraviolet light can trigger the rapid polymerization of surface or shallow monomers within seconds to minutes to form a preliminary cross-linked network and precisely control the reaction area. The thermal initiator continues to generate free radicals in the subsequent heating stage, penetrating into deep areas or shadow areas that light cannot reach to ensure that the overall conversion rate is maximized.
[0043] S9, 15% to 25% of the total weight of the core layer monomer composition and an emulsifier are mixed at a mass ratio of 10 to 15:1 to prepare a shell layer pre-emulsion, and the shell layer pre-emulsion is added to the double-layer prepolymer in 4 times, each time at an interval of 30 minutes, and reacted at 70° C. for 3 hours to obtain a three-layer prepolymer; Sodium dodecyl sulfate in the emulsifier is preferentially adsorbed on the interface between the middle layer and the shell layer, reducing the interfacial tension between the shell monomer and the middle layer and promoting uniform wrapping of the shell layer.
[0044] The long-chain PEO of octylphenol polyoxyethylene ether in the emulsifier dynamically adjusts adsorption during the shell polymerization process to adapt to the changes in the hydrophobicity of the shell monomer.
[0045] The synergistic effect of emulsifiers can enhance the shear resistance of latex particles under high-speed stirring or high solid content, thereby avoiding shell damage.
[0046] The pre-emulsion is added in multiple times, which can achieve the phased polymerization of the shell layer and avoid the embrittlement of the shell layer caused by premature cross-linking of dodecafluoroheptyl methacrylate.
[0047] In addition, adding dodecafluoroheptyl methacrylate in batches can achieve a concentration gradient of fluorine from the surface to the inside. The high fluorine content in the surface layer enhances the hydrophobicity, while the low fluorine content in the bottom layer maintains adhesion with the middle layer.
[0048] S10, cooling to room temperature, filtering, and adjusting the solid content to 40% to 45% to obtain the target product.
[0049] Timely cooling to room temperature can slow down or stop the activity of residual free radicals and avoid excessive polymerization or cross-linking that leads to a broadening of the molecular weight distribution.
[0050] Filtration and solid content adjustment respectively improve the purity of the product and optimize product performance from the perspective of application adaptability, ensuring that the core-shell material achieves the best balance between functionality and processability.
[0051] In order to facilitate further understanding of the present invention, several embodiments and comparative examples of the present invention are given below: Embodiment 1: S1. Based on a total of 100 parts by weight, 75 parts by weight of methyl methacrylate, 24 parts by weight of butyl acrylate, and 1 part by weight of divinylbenzene are mixed to prepare a core layer monomer composition; S2. Based on the sum of the weight parts being 100, 65 parts by weight of isooctyl acrylate, 28 parts by weight of styrene, and 7 parts by weight of hydroxyethyl acrylate are mixed to prepare an intermediate layer monomer composition; S3, based on a total of 100 parts by weight, 80 parts by weight of ethyl acrylate and 20 parts by weight of dodecafluoroheptyl methacrylate were mixed to prepare a shell monomer composition; S4, compounding sodium lauryl sulfate and octylphenol polyoxyethylene ether in a mass ratio of 1:3 to form an emulsifier for standby use; S5, mixing the core layer monomer composition, the emulsifier and the deionized water in a mass ratio of 17:1:280, and pre-emulsifying for 10 minutes under high-speed shearing; S6, adding emulsifier three times during the polymerization process, the mass ratio of emulsifier added each time to the core layer monomer composition is 1:45, each time interval is 20 minutes, to obtain a core layer pre-emulsion; S7, adding 1% of the total weight of the core layer monomer composition of ammonium persulfate to the core layer pre-emulsion, heating to 75° C. and reacting for 1 hour to obtain a core layer prepolymer; S8, adding 40% of the total weight of the intermediate layer monomer composition, 1% of the total weight of the core layer monomer composition, and 2% of the total weight of the TPO initiator to the core layer prepolymer, prepolymerizing for 30 minutes under 50W ultraviolet light irradiation, then heating to 65°C, adding 1% of the total weight of the core layer monomer composition, and continuing the reaction for 2 hours to obtain a double-layer prepolymer; S9, mixing 20% of the total weight of the core layer monomer composition with an emulsifier in a mass ratio of 12:1 to prepare a shell layer pre-emulsion, dynamically adding the shell layer pre-emulsion to the double-layer prepolymer 4 times, each time at an interval of 30 minutes, and reacting at 70° C. for 3 hours to obtain a three-layer prepolymer; S10, cooling to room temperature, filtering, and adjusting the solid content to 40% to obtain the target product.
[0052] Embodiment 2: S1. Based on a total weight of 100 parts, 70 parts by weight of methyl methacrylate, 28 parts by weight of butyl acrylate, and 2 parts by weight of divinylbenzene are mixed to prepare a core layer monomer composition; S2. Based on the sum of parts by weight being 100, 60 parts by weight of isooctyl acrylate, 30 parts by weight of styrene, and 10 parts by weight of hydroxyethyl acrylate are mixed to prepare an intermediate layer monomer composition; S3, based on a total of 100 parts by weight, 70 parts by weight of ethyl acrylate and 30 parts by weight of dodecafluoroheptyl methacrylate were mixed to prepare a shell monomer composition; S4, compounding sodium lauryl sulfate and octylphenol polyoxyethylene ether in a mass ratio of 1:3 to form an emulsifier for standby use; S5, mixing the core layer monomer composition, the emulsifier and the deionized water in a mass ratio of 17:1:280, and pre-emulsifying for 10 minutes under high-speed shearing; S6, adding emulsifier three times during the polymerization process, the mass ratio of emulsifier added each time to the core layer monomer composition is 1:45, each time interval is 20 minutes, to obtain a core layer pre-emulsion; S7, adding 1% of the total weight of the core layer monomer composition of ammonium persulfate to the core layer pre-emulsion, heating to 75° C. and reacting for 1 hour to obtain a core layer prepolymer; S8, adding 40% of the total weight of the intermediate layer monomer composition, 1% of the total weight of the core layer monomer composition, and 2% of the total weight of the TPO initiator to the core layer prepolymer, prepolymerizing for 30 minutes under 50W ultraviolet light irradiation, then heating to 65°C, adding 1% of the total weight of the core layer monomer composition, and continuing the reaction for 2 hours to obtain a double-layer prepolymer; S9, mixing 20% of the total weight of the core layer monomer composition with an emulsifier in a mass ratio of 12:1 to prepare a shell layer pre-emulsion, dynamically adding the shell layer pre-emulsion to the double-layer prepolymer 4 times, each time at an interval of 30 minutes, and reacting at 70° C. for 3 hours to obtain a three-layer prepolymer; S10, cooling to room temperature, filtering, and adjusting the solid content to 40% to obtain the target product.
[0053] Example 3 S1. Based on a total of 100 parts by weight, 75 parts by weight of methyl methacrylate, 24 parts by weight of butyl acrylate, and 1 part by weight of divinylbenzene are mixed to prepare a core layer monomer composition; S2. Based on the sum of the weight parts being 100, 65 parts by weight of isooctyl acrylate, 28 parts by weight of styrene, and 7 parts by weight of hydroxyethyl acrylate are mixed to prepare an intermediate layer monomer composition; S3, based on a total of 100 parts by weight, 80 parts by weight of ethyl acrylate and 20 parts by weight of dodecafluoroheptyl methacrylate were mixed to prepare a shell monomer composition; S4, compounding sodium lauryl sulfate and octylphenol polyoxyethylene ether in a mass ratio of 1:4 to form an emulsifier for standby use; S5, mixing the core layer monomer composition, the emulsifier and the deionized water in a mass ratio of 17:1:280, and pre-emulsifying for 10 minutes under high-speed shearing; S6, adding emulsifier three times during the polymerization process, the mass ratio of emulsifier added each time to the core layer monomer composition is 1:45, each time interval is 20 minutes, to obtain a core layer pre-emulsion; S7, adding 1% of the total weight of the core layer monomer composition of ammonium persulfate to the core layer pre-emulsion, heating to 75° C. and reacting for 1 hour to obtain a core layer prepolymer; S8, adding 40% of the total weight of the intermediate layer monomer composition, 1% of the total weight of the core layer monomer composition, and 2% of the total weight of the TPO initiator to the core layer prepolymer, prepolymerizing for 30 minutes under 50W ultraviolet light irradiation, then heating to 65°C, adding 1% of the total weight of the core layer monomer composition, and continuing the reaction for 2 hours to obtain a double-layer prepolymer; S9, mixing 20% of the total weight of the core layer monomer composition with an emulsifier in a mass ratio of 12:1 to prepare a shell layer pre-emulsion, dynamically adding the shell layer pre-emulsion to the double-layer prepolymer 4 times, each time at an interval of 30 minutes, and reacting at 70° C. for 3 hours to obtain a three-layer prepolymer; S10, cooling to room temperature, filtering, and adjusting the solid content to 40% to obtain the target product.
[0054] Comparative Example 1: S1. Based on a total of 100 parts by weight, 75 parts by weight of methyl methacrylate, 24 parts by weight of butyl acrylate, and 1 part by weight of divinylbenzene are mixed to prepare a core layer monomer composition; S2. Based on the sum of the weight parts being 100, 65 parts by weight of isooctyl acrylate, 28 parts by weight of styrene, and 7 parts by weight of hydroxyethyl acrylate are mixed to prepare an intermediate layer monomer composition; S3, based on a total of 100 parts by weight, 80 parts by weight of ethyl acrylate and 20 parts by weight of dodecafluoroheptyl methacrylate were mixed to prepare a shell monomer composition; S4, compounding sodium lauryl sulfate and octylphenol polyoxyethylene ether in a mass ratio of 1:3 to form an emulsifier for standby use; S5, mixing the core layer monomer composition, the emulsifier and the deionized water in a mass ratio of 17:2:280, and pre-emulsifying for 10 minutes under high-speed shearing to obtain a core layer pre-emulsion; S6, adding 1% of the total weight of the core layer monomer composition of ammonium persulfate to the core layer pre-emulsion, heating to 75° C. and reacting for 1 hour to obtain a core layer prepolymer; S7, adding 40% of the total weight of the intermediate layer monomer composition, 1% of the total weight of the core layer monomer composition, and 2% of the total weight of the TPO initiator to the core layer prepolymer, prepolymerizing for 30 minutes under 50W ultraviolet light irradiation, then heating to 65°C, adding 1% of the total weight of the core layer monomer composition, and continuing the reaction for 2 hours to obtain a double-layer prepolymer; S8, mixing 20% of the total weight of the core layer monomer composition with an emulsifier in a mass ratio of 12:1 to prepare a shell layer pre-emulsion, adding the shell layer pre-emulsion to the double-layer prepolymer, and reacting at 70° C. for 3 hours to obtain a three-layer prepolymer; S9, cool to room temperature, filter, and adjust the solid content to 40% to obtain the target product.
[0055] Comparative Example 2: S1. Based on a total of 100 parts by weight, 75 parts by weight of methyl methacrylate, 24 parts by weight of butyl acrylate, and 1 part by weight of divinylbenzene are mixed to prepare a core layer monomer composition; S2. Based on the sum of the weight parts being 100, 65 parts by weight of isooctyl acrylate, 28 parts by weight of styrene, and 7 parts by weight of hydroxyethyl acrylate are mixed to prepare an intermediate layer monomer composition; S3, based on a total of 100 parts by weight, 80 parts by weight of ethyl acrylate and 20 parts by weight of dodecafluoroheptyl methacrylate were mixed to prepare a shell monomer composition; S4, compounding sodium lauryl sulfate and octylphenol polyoxyethylene ether in a mass ratio of 1:3 to form an emulsifier for standby use; S5, mixing the core layer monomer composition, the emulsifier and the deionized water in a mass ratio of 17:1:280, and pre-emulsifying for 10 minutes under high-speed shearing; S6, adding emulsifier three times during the polymerization process, the mass ratio of emulsifier added each time to the core layer monomer composition is 1:45, each time interval is 20 minutes, to obtain a core layer pre-emulsion; S7, adding 1% of the total weight of the core layer monomer composition of ammonium persulfate to the core layer pre-emulsion, heating to 75° C. and reacting for 1 hour to obtain a core layer prepolymer; S8, adding 40% of the total weight of the intermediate layer monomer composition and 1% of the total weight of the core layer monomer composition to the core layer prepolymer, raising the temperature to 65° C., adding 1% of the total weight of ammonium persulfate to the core layer monomer composition, and continuing the reaction for 2 hours to obtain a double-layer prepolymer; S9, mixing 20% of the total weight of the core layer monomer composition with an emulsifier in a mass ratio of 12:1 to prepare a shell layer pre-emulsion, dynamically adding the shell layer pre-emulsion to the double-layer prepolymer 4 times, each time at an interval of 30 minutes, and reacting at 70° C. for 3 hours to obtain a three-layer prepolymer; S10, cooling to room temperature, filtering, and adjusting the solid content to 40% to obtain the target product.
[0056] Comparative Example 3: S1. According to the total weight of 160 parts, 75 parts by weight of methyl methacrylate, 24 parts by weight of butyl acrylate, 1 part by weight of divinylbenzene, 26 parts by weight of isooctyl acrylate, 11.2 parts by weight of styrene, 2.8 parts by weight of hydroxyethyl acrylate, 16 parts by weight of ethyl acrylate, and 4 parts by weight of dodecafluoroheptyl methacrylate are mixed to form a monomer composition. S2, compounding sodium lauryl sulfate and octylphenol polyoxyethylene ether in a mass ratio of 1:3 to form an emulsifier for standby use; S3, mixing the monomer composition, the emulsifier and the deionized water in a mass ratio of 17:1:280, and pre-emulsifying for 10 minutes under high-speed shearing; S4, adding emulsifier three times during the polymerization process, the mass ratio of emulsifier added each time to the monomer composition is 1:45, each time interval is 20 minutes, to obtain a pre-emulsion; S5, adding 1% of the total weight of the monomer composition of ammonium persulfate to the pre-emulsion, heating to 75 ° C for 4 hours to obtain a prepolymer; S6. Cool to room temperature, filter, and adjust the solid content to 40% to obtain the target product.
[0057] The intrinsic viscosity of the ultra-high viscosity polyacrylate foaming regulators prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the test results are as follows:
[0058] The polyacrylate foaming regulator, polyvinyl chloride and auxiliary agent prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were prepared into test samples according to the proportions shown in the following table. The proportions are shown in the following table:
[0059] Test samples were prepared according to the above ratios, and performance tests were performed on each sample. The results are as follows:
[0060] According to the above data: 1. Example 1 has a complete core-shell structure, strong interface bonding, optimal mechanical properties and thermal stability, and its performance is similar to that of Example 2. However, the content of dodecafluoroheptyl methacrylate in the shell structure of Example 2 is higher, and its hydrophobicity is slightly better than that of Example 1. In Example 3, the addition ratio of the emulsifier is increased, which effectively improves the dispersibility, resulting in the lowest melt index.
[0061] 2. Comparative Example 1: Based on Example 1, the method of adding the emulsifier was adjusted, and the dynamic addition in batches was no longer adopted, resulting in poor emulsification effect, resulting in poor performance in terms of gloss, compression strength and tensile strength.
[0062] 3. Comparative Example 2, based on Example 1, no longer uses photothermal dual initiation, but only uses thermal initiation, which leads to insufficient crosslinking and shorter chain segments, thus affecting the comprehensive performance of the foaming material.
[0063] 4. Comparative Example 3 is based on Example 1, but no longer uses a core-shell structure. The monomers are mixed and polymerized, and the molecular weight is low and the distribution is wide, resulting in its overall performance being backward.
[0064] According to the embodiments of the present invention as described above, these embodiments do not describe all the details in detail, nor do they limit the invention to the only specific embodiments. Obviously, based on the above description, many modifications and changes can be made. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can make good use of the present invention and the modified use based on the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a polyacrylate foaming regulator, characterized in that: The following steps are involved: S1, methyl methacrylate, butyl acrylate and divinylbenzene are mixed to form a core layer monomer composition for later use; S2, mixing isooctyl acrylate, styrene and hydroxyethyl acrylate to form an intermediate layer monomer composition for later use; S3, mixing ethyl acrylate and dodecafluoroheptyl methacrylate to form a shell monomer composition for later use; S4, mixing sodium lauryl sulfate and octylphenol polyoxyethylene ether to form an emulsifier for standby use; S5, mixing the core layer monomer composition, the emulsifier and the deionized water, and stirring for pre-emulsification for 10 minutes; S6, adding emulsifier three times, each time with an interval of 20 minutes, to obtain a nuclear layer pre-emulsion; S7, adding ammonium persulfate to the core layer pre-emulsion, heating to 75° C. and reacting for 1 h to obtain a core layer prepolymer; S8, adding the middle layer monomer composition, hexamethylphosphoric triamide and TPO initiator to the core layer prepolymer, prepolymerizing under ultraviolet light, then heating to 65° C., adding ammonium persulfate and continuing the reaction for 2 h to obtain a double-layer prepolymer; S9, mixing the shell monomer composition with an emulsifier to prepare a shell pre-emulsion, adding the shell pre-emulsion to the double-layer prepolymer 4 times, each time at an interval of 30 minutes, and reacting at 70° C. for 3 hours to obtain a three-layer prepolymer; S10, cooling to room temperature, filtering, and adjusting the solid content to 40% to 45% to obtain the target product.
2. The method for preparing the polyacrylate foaming regulator according to claim 1, characterized in that: In step S1, the mass ratio of methyl methacrylate, butyl acrylate and divinylbenzene is 60-80:20-30:0.5-2.
3. The method for preparing the polyacrylate foaming regulator according to claim 1, characterized in that: In step S2, the mass ratio of isooctyl acrylate, styrene and hydroxyethyl acrylate is 10-14:4-6:1-2.
4. The method for preparing the polyacrylate foaming regulator according to claim 1, characterized in that: In step S3, the mass ratio of ethyl acrylate to dodecafluoroheptyl methacrylate is 7-9:1-3.
5. The method for preparing the polyacrylate foaming regulator according to claim 1, characterized in that: In step S4, the mass ratio of sodium dodecyl sulfate to octylphenol polyoxyethylene ether is 1:2-4.
6. The method for preparing the polyacrylate foaming regulator according to claim 1, characterized in that: In step S5, the mass ratio of the core layer monomer composition, the emulsifier, and the deionized water is 15-20:1-1.2:250-350.
7. The method for preparing the polyacrylate foaming regulator according to claim 1, characterized in that: In step S5, the stirring speed is 8000-12000 r / min.
8. The method for preparing the polyacrylate foaming regulator according to claim 1, characterized in that: In step S6, the mass ratio of the emulsifier added each time to the core layer monomer composition in step S1 is 1:40-50.
9. The method for preparing the polyacrylate foaming regulator according to claim 1, characterized in that: In step S9, the mass ratio of the shell monomer to the emulsifier is 10-15:1.
Citation Information
Patent Citations
Transparent polyvinyl chloride toughening modifier with three-layer nuclear shell structure and preparation method thereof
CN101544731A
Silicone-acrylic emulsion and preparation method thereof
CN109400791A
Preparation method of antibacterial and antiviral water-based hydroxyl acrylate emulsion
CN116655943A
Fluorine-silicon-containing polymer with multi-layer core-shell structure, and preparation method and application of resin composition comprising fluorine-silicon-containing polymer with multi-layer core-shell structure
CN119463061A
Method for preparing microcapsules by double emulsion
US20180185809A1
Cited By
Acrylate copolymer and preparation method thereof
CN120504784A
Acrylate copolymer and preparation method thereof
CN120504784B